Autonomous fundamental motor skills in the school environment: a cross-sectional study - Anderson Dos Santos Carvalho; Leonardo Santos Lopes da Silva; Pedro Pugliesi Abdalla; Nilo César Ramos; Jorge Mota; Dalmo Roberto Lopes Machado (Desafio Singular, 2022)
Autonomous fundamental motor skills (AFMS) are understood as movements practiced in a spontaneous, voluntary manner, without any instruction or command. The aim of the study was to compare the frequency of occurrence and the quality of performance of AFMS in children during recess and Physical Education (PE) classes. Elementary school students (n=148) from a private school were observed during recess and PE classes and had their AFMS classified by stages (initial; elementary-emergent; proficient). All AFMS were identified in recess and PE classes, except jump. Most skills were classified in the elementary-emergent stage and were slightly more frequent during PE classes, both in the locomotor (27% vs 23%) and manipulative (31% vs 13%) categories. The frequency of occurrence of AFMS was low and the classification showed poor quality at all times observed. Recess was statistically (p < 0.05) less favorable for motor development in 60% of AFMS. The low frequency of AFMS, especially during recess, and poor classification of motor repertoire suggest the need for measures to reverse the motor deficit in the school environment. Strategies are needed to promote AFMS in the school context so that they are more diverse and challenging.